News Writing - Mckane, Anna (SAGE Publications Ltd, 2014)
The ability to hone and craft an eye-catching news story is fundamental to good journalism. It is an essential skill that the young journalist of today must carry with them. The growth of online journalism and the use of social media has meant that the skills required in news writing are evolving, opening up fresh challenges and exciting new possibilities. Anna McKane's News Writing takes you step-by-step through the key aspects of writing news on both print and online platforms, equipping you with all that you need to become an